Designing a Simulation Model for the Milk Carton Filling Line - Ghufran Khalil Joad; Salih Sufian Munth (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This research built a simulation model of the cans line mobilization process yogurt in the Mosul dairy factory to see average waiting time per can and the average number of cans that remain in the queue before the filling process. Where the model was built using Microsoft Excel and queuing model used for this study is the kind of M/M/1: (FeFs,00,00). The results are that the time of waiting for each packet in the queue about (17) minutes and the average number of cans in the queue is (206) can of the total cans (1440 packqge) for that day.